1999
DOI: 10.1177/088307389901401104
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Magnetic Resonance Imaging Examination of Normal Term Neonates: A Pilot Study

Abstract: This pilot study's aim was to determine, using magnetic resonance imaging (MRI), if and to what extent asymptomatic intracranial hemorrhage occurs in normal term neonates after uncomplicated vaginal deliveries. Eight normal, term, vaginally delivered infants and three cesarean-section deliveries used as controls underwent cranial MRI. No sedation was administered. Small subdural hematomas of the falx cerebri or tentorium cerebelli were found in half of those with an uneventful vaginal delivery. Pediatric follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 6 publications
1
29
1
Order By: Relevance
“…[20][21][22] The incidence of SDH (46%) is significantly higher in our study than in previous reports. Our Note:-C/S indicates cesarean delivery; SVD, spontaneous vaginal delivery.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…[20][21][22] The incidence of SDH (46%) is significantly higher in our study than in previous reports. Our Note:-C/S indicates cesarean delivery; SVD, spontaneous vaginal delivery.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies conducted in an effort to determine the incidence and natural history of asymptomatic SDH in the neonate have been limited by the use of low-field-strength (0.2T) MR imaging, small patient numbers, or variable timing of imaging after birth. [20][21][22][23] The purpose of this study was to determine the normal incidence, size, appearance, and distribution of SDH in asymptomatic term neonates as detected by US and 1.5T MR imaging within 72 hours of birth. In addition, we prospectively studied the natural history of these hemorrhages.…”
mentioning
confidence: 99%
“…16 However, MRI revealed that asymptomatic SDH at birth is common. [17][18][19] Some studies report a prevalence as high as 50%, 20 although no study so far reports persistence of SDH present at birth beyond 4 weeks. 21 The purpose of this study was to review the incidence of SDH in newborns with congenital heart disease undergoing MRI brain scans as part of a perioperative research protocol and to explore the relationship between SDH and hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of asymptomatic neonatal SDH in published literature ranges from 8% to 45%. [17][18][19]21 One previous study of SDH in a much smaller cohort of newborns with congenital heart disease identified preoperative SDH in 11 out of 21 (52%). 20 It is usually suggested that these SDHs originate from tearing of the dura or bridging veins by molding of the cranium during birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation